Bioreaction Engineering Leading to Efficient Synthesis of L‐Glyceraldehyd‐3‐Phosphate. Issue 3 (24th January 2017) - Molla, Getachew S.; Kinfu, Birhanu M.; Chow, Jennifer; Streit, Wolfgang; Wohlgemuth, Roland; Liese, Andreas
Abstract: Enantiopure L‐glyceraldehyde‐3‐phosphate (L‐GAP) is a useful building block in natural biological and synthetic processes. A biocatalytic process using glycerol kinase from Cellulomonas sp. (EC 2.7.1.30) catalyzed phosphorylation of L‐glyceraldehyde (L‐GA) by ATP is used for the synthesis of L‐GAP. L‐GAP has a half‐life of 6.86 h under reaction conditions. The activity of this enzyme depends on the Mg 2+ to ATP molar ratio showing maximum activity at the optimum molar ratio of 0.7. A kinetic model is developed and validated showing a 2D correlation of 99.9% between experimental and numerical data matrices. The enzyme exhibits inhibition by ADP, AMP, methylglyoxal and Ca 2+, but not by L‐GAP and inorganic orthophosphate. Moreover, equal amount of Ca 2+ exerts a different degree of inhibition relative to the activity without the addition of Ca 2+ depending on the Mg 2+ to ATP molar ratio. If the Mg 2+ to ATP molar ratio is set to be at the optimum value or less, inorganic hexametaphosphate (PPi6) suppresses the enzyme activity; otherwise PPi6 enhances the enzyme activity. Based on reaction engineering parameters such as conversion, selectivity and specific productivity, evaluation of different reactor types reveals that batchwise operation via stirred‐tank reactor is the most efficient process for the synthesis of L‐GAP. Abstract : Enantiopure L‐glyceraldehyde‐3‐phosphate (L‐GAP) is a useful building block in natural biological and synthetic processes as well as in medical treatment as a blocker of in vivo enzymatic reactions. A biocatalytic process using glycerol kinase from Cellulomonas sp. (EC 2.7.1.30) catalyzed phosphorylation of L‐glyceraldehyde (L‐GA) by ATP requiring a cofactor Mg 2+ was designed for the synthesis of L‐GAP. The target product L‐GAP has a half‐life of 6.86 h under reaction conditions applied. The activity of the enzyme depends on the Mg 2+ to ATP molar ratio showing maximum activity at the optimum molar ratio of 0.7.